Большой баклан Phalacrocorax carbo sinensis в дельте Дона - Лебедева, Н.В.; Ломадзе, Н.Х.; Савицкий, Р.М. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2008)
Data on breeding of the Cormorant continental subspecies Phalacrocorax carbo sinensis on islands in the Don Delta are presented. The structure of the mixed breeding colony has been studied. Rooks Corvus frugilegus and 4 species of herons (Grey Heron Ardea cinerea, Little Egret Egretta garzetta, Squacco Heron Ardeola ralloides and Night Heron Nycticorax nycticorax) nested in this colony together with Cormorants in different years. Changes in structure are analyzed for the 30-years period of the existence of this colony. Data on phenology, breeding biology of the Cormorant, dynamics of its trophic niche during the nesting period are discussed.